2007
DOI: 10.1002/mds.21578
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa responsiveness in disorders with parkinsonism: A review of the literature

Abstract: A literature review was conducted to investigate whether or not levodopa (LD) responsiveness (LR) is a useful criterion in the diagnosis of parkinsonian disorders. Although LR does appear to differ among the parkinsonian disorders, there is considerable confusion in the literature. While most patients with Parkinson's disease (PD) have a sustained benefit from LD, a small minority of patients with documented PD do not respond. The literature suggests that the LR rate is higher for multiple system atrophy (MSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 74 publications
1
43
0
1
Order By: Relevance
“…A major feature of LID appears to be overactivity of the direct striatal pathway, but the pathophysiology of LID is complex, likely involving both pre-and postsynaptic alterations in the nigrostriatal system (Cenci and Lundblad 2006;Cenci and Lindgren 2007). Presynaptic dopaminergic denervation is presumed to be necessary for the development of LID, illustrated by the fact that healthy subjects with an intact presynaptic dopaminergic system do not develop LID (Constantinescu et al 2007). Moreover, the development of LID presumably relates to an interaction between the endogenous dopaminergic denervation and application of levodopa, an exogenous dopamine precursor (Cenci and Lundblad 2006).…”
Section: Motor Complications Of Therapydyskinesiasmentioning
confidence: 99%
“…A major feature of LID appears to be overactivity of the direct striatal pathway, but the pathophysiology of LID is complex, likely involving both pre-and postsynaptic alterations in the nigrostriatal system (Cenci and Lundblad 2006;Cenci and Lindgren 2007). Presynaptic dopaminergic denervation is presumed to be necessary for the development of LID, illustrated by the fact that healthy subjects with an intact presynaptic dopaminergic system do not develop LID (Constantinescu et al 2007). Moreover, the development of LID presumably relates to an interaction between the endogenous dopaminergic denervation and application of levodopa, an exogenous dopamine precursor (Cenci and Lundblad 2006).…”
Section: Motor Complications Of Therapydyskinesiasmentioning
confidence: 99%
“…Although most patients with PSP do not benefit from treatment with levodopa, about 30 % of patients have some improvement initially or at early stages of the disease [3]. Recent studies [15] suggested a further differentiation of the PSP syndrome into (i) Richardson's syndrome (RS) which corresponds well to 'classical' PSP, and (ii) into a syndrome formerly characterised as atypical PSP with asymmetric onset, tremor and initial response to levodopa, which now is described as PSP-parkinsonism (PSP-P).…”
Section: Introductionmentioning
confidence: 98%
“…Considering side effects, LD-induced dyskinesias seems to be rare, however, some can develop worsening of motor features and dystonia 33 . A retrospective study involving 12 autopsy-confirmed cases of PSP, found a positive response in four of 11 patients using LD, and in two of 6 using dopamine agonist.…”
Section: Symptomatic Treatmentmentioning
confidence: 99%
“…Drugs directed to systems other than dopaminergic, such as serotonergic, noradrenergic, and cholinergic, were also tried in PSP. Serotoninergic drugs, such as selective serotonin reuptake inhibitors, 5-hydroxytryptophan, and methysergide have no confirmed benefit in PSP 31,33 , neither have cholinergic drugs, such as AChE inhibitors, and muscarinic agonists 36 . Concerning cognitive deficit in PSP, rivastigmine lead to a slight improvement in specific function in a small series with five cases 37 .…”
Section: Symptomatic Treatmentmentioning
confidence: 99%